Implementation of the Uncollectible Receivables Settlement Policy in the Provincial Government of the Special Region of Jakarta - Utari, Nikesari Puji; Setyowati, Milla S. (Journal of Public Representative and Society Provision, 2024)
The purpose of this article is to examine the various implementations of policies related to the resolution of uncollectible regional debts that have been carried out by the Provincial Government of the Special Capital Region of Jakarta. Regional debts are important assets that can be viewed from the perspective of both potential utilization and accountability. This study employs a literature review, in which the author analyzes the extent to which the implementation of policies for resolving uncollectible debts in the Special Capital Region of Jakarta has been effective. The various implementations already applied are expected to provide certainty regarding the collection of regional debts, as they represent a potential source of revenue for the local government.